A new approach to classical relevance. - De Bal, Inge; Verdée, Peter (Studia Logica, 2015)
n this paper we present a logic that determines when implications in a classical logic context express a relevant connection between antecedent and consequent. In contrast with logics in the relevance logic literature, we leave classical negation intact - in the sense that the law of non-contradiction can be used to obtain relevantly implications, as long as there is a connection between antecedent and consequent. On the other hand, we give up the requirement that our theory of relevance can define a new standard of deduction. We present and argue for a list of requirements that such a logical theory of classical relevance needs to meet and go on to formulate a system that respects each of these requirements. The presented system is a monotonic and transitive logic that extends the relevance logic ℜ with a richer relevant implication that allows for Disjunctive Syllogism and similar rules. This is achieved by interpreting the logical symbols in the antecedents in a stronger way than the logical symbols in consequents. A proof theory and an algebraic semantics are formulated and interesting metatheorems (soundness, completeness and the fact that it satisfies the requirements for classical relevance) are proven. Finally we give a philosophical motivation for our non-standard relevant implication and the asymmetric interpretation of antecedents and consequents.